Heavy metal contamination in urban agriculture: Evidence from Nairobi - Murphy, Mike; Wachira, Githenya; Onyango, Cecilia; Hoffmann, Vivian (Springer, 2025)
Agricultural production in urban areas plays an important role in food systems in low- and middle-income countries but also may also be subject to significant environmental hazards. We analyze samples of leafy greens grown on farms in Nairobi County selected via random geographical sampling for three heavy metals harmful to human health (lead, cadmium, and mercury). The mean levels of contamination are 0.68 ppm for lead, 0.09 ppm for cadmium, and 0.11 ppm for mercury. Spatial analysis shows that crops grown closer to roadways have higher levels of lead contamination and those grown near industrial sites have higher levels of mercury. We disaggregate our sample and test native greens and kale sourced from outside Nairobi as potential substitutes for urban-grown kale but find similar contamination levels. We estimate that 71% of adults and 69% of children in our sample are exposed to lead in excess of daily reference levels, with 12% of adults exceeding levels for cadmium and 52% exceeding levels for mercury via leafy greens alone. Using representative data for Nairobi and results from sampling leafy greens from local wholesale markets, we estimate similar dietary exposure levels for the population of the city as a whole. Our findings demonstrate the importance of systematic surveillance of foods in LMICs for heavy metals and the need to identify and mitigate sources of contamination.